Gender Gaps in Latin American Labor Markets: Implications from an Estimated Search Model - Mauricio Tejada; Claudia Piras; Luca Flabbi; Monserrat Bustelo (Institute of Labor Economics (IZA), 2021)
We develop and estimate a search model that captures the specific characteristics of Latin America and Caribbean (LAC) labor markets and the crucial differences between men and women. Labor force participation decisions are integrated in the labor market dynamics, taking into account sample selection over unobservables. The model is estimated on four LAC countries (Argentina, Chile, Colombia and Mexico) and on three education levels (Primary, Secondary and Tertiary). We use the estimated model to study changes in gender gaps and in output implied by policies that increase the labor force participation of women. We focus on four policies: an increase in the provision of child care, an increase in average female productivity, a gender-based contribution rate for formal employees, and changes in formality and informality costs. We find that the impact on the extensive margin of the female labor supply is the main channel responsible for the policy-induced increase in output.
Keywords: J24; J3; J64; O17; 330; gender gaps; female labor force participation; labor market frictions; search and matching; Nash bargaining; informality